2003
DOI: 10.1128/aac.47.3.878-882.2003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tetracycline Resistance Genes in Oral Bacteria

Abstract: Tetracycline is a broad-spectrum antibiotic used in humans, animals, and aquaculture; therefore, many bacteria from different ecosystems are exposed to this antibiotic. In order to determine the genetic basis for resistance to tetracycline in bacteria from the oral cavity, saliva and dental plaque samples were obtained from 20 healthy adults who had not taken antibiotics during the previous 3 months. The samples were screened for the presence of bacteria resistant to tetracycline, and the tetracycline resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
105
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 33 publications
12
105
1
1
Order By: Relevance
“…The tet(W) gene has been originally identified in Butyrivibrio fibrisolvens isolate from the bovine rumen, subsequently found in the Clostridium-related human fecal anaerobe bacterium K10 and in human Fusobacterium and Bifidobacterium isolates and recently frequently isolated in bacteria from the human oral cavity (Sco� et al, 1997(Sco� et al, , 2000Villedieu et al, 2003). It was shown to be located on the conjugative transposon TnB1230 .…”
Section: Ribosomal Protection Determinantsmentioning
confidence: 99%
“…The tet(W) gene has been originally identified in Butyrivibrio fibrisolvens isolate from the bovine rumen, subsequently found in the Clostridium-related human fecal anaerobe bacterium K10 and in human Fusobacterium and Bifidobacterium isolates and recently frequently isolated in bacteria from the human oral cavity (Sco� et al, 1997(Sco� et al, , 2000Villedieu et al, 2003). It was shown to be located on the conjugative transposon TnB1230 .…”
Section: Ribosomal Protection Determinantsmentioning
confidence: 99%
“…These genes are distinct from previously described ribosome protection genes, with the highest identities being 68% [to Tet(W)] and 76% [to Tet(32)] at the corresponding amino acid level. tet(W) is one of the most widespread tetracycline resistance genes in environmental samples (1,23).Copies of tet(W) found in environmentally and phylogenetically distinct bacterial isolates (2, 20) have remarkable sequence conservation, which argues for the extensive rapid transfer of this gene in nature. Previous work showed that tet(W) could be transferred at high frequencies (10 Ϫ2 to 10 Ϫ5…”
mentioning
confidence: 99%
“…These genes are distinct from previously described ribosome protection genes, with the highest identities being 68% [to Tet(W)] and 76% [to Tet(32)] at the corresponding amino acid level. tet(W) is one of the most widespread tetracycline resistance genes in environmental samples (1,23).…”
mentioning
confidence: 99%
“…is the most extensively studied antibiotic resistance gene in terms of molecular ecology 9) and has been found among numerous species of Gram-negative and Gram-positive bacteria including not only human pathogens 6,20,22,38) but also bacteria obtained from several terrestrial environments associated with human activity 9) such as in agriculture 33) , groundwater 8) , and daily diets 14,16,26,39) . Tet(M) is often accompanied by mobile elements such as plasmids and transposons, such associations contributing to the wide distribution of this gene in bacterial genera obtained from different environments 9) .…”
mentioning
confidence: 99%